Does earnings management affect idiosyncratic volatility - Pereira, Cláudia (2017)
This paper examines the association between earnings management and firm-specific return volatility for a sample of firms listed on the London Stock Exchange. Identifying the determinants of idiosyncratic volatility has been a topical issue since the Campbell et al. (2001) study which documents a noticeable increase in average firm-level volatility across time. Using panel data, we find that poor information environments resulting from earnings management is associated with higher firm-specific return volatility. This finding is consistent with the noise-based approach of firm-specific return volatility. In addition we provide empirical evidence that such association gets stronger when combining accruals quality and the dispersion in analysts’ forecast to describe a poor information environment. Furthermore, we find that poor information environment, leverage and the intensity of information disclosure tend to increase idiosyncratic return volatility, while older, more profitable and larger firms tend exhibit lower levels of idiosyncratic volatility. These results are likely to contribute to the debate on whether firm-specific return volatility captures more firm-specific information being impounded in stock prices or essentially reflects noise.